Evaluating the Potential of Artificial Intelligence in Orthopedic Surgery for Value-based Healthcare - Tariq, Aftab; Gill, Ahmad Yousaf; Hussain, Hafiz Khawar (Information Technology and Science (ITScience), 2023)
The potential of artificial intelligence (AI) to transform value-based healthcare in the area of orthopedic surgery is examined in this research. Orthopedic surgeons and healthcare systems may improve patient outcomes, increase efficiency, and alter care delivery by combining AI algorithms, cutting-edge data analytics, and novel technology. Through case studies and success stories, the article provides a thorough study of the advantages and prospects provided by AI in orthopedic surgery. These instances demonstrate how AI has been successfully applied to several facets of orthopedic surgery, including as diagnosis, planning of the surgical course, surgical navigation, postoperative care, and resource allocation. The ethical and legal ramifications of using AI are also discussed in the study, with a focus on patient autonomy, privacy, accountability, and any potential effects on the healthcare workforce. The potential applications of AI in orthopedic surgery are examined, together with developments in preoperative planning, surgical robotics, remote monitoring, predictive analytics, personalised medicine, research, and innovation. The promise of AI in orthopedic surgery is obvious, despite issues with data quality, privacy, algorithm biases, and legal constraints. The ethical and appropriate application of AI technology in orthopedic surgery has the potential to significantly enhance patient outcomes, lower complications, boost efficiency, and change the way healthcare is provided. This study lays the groundwork for future study and application in the field of orthopedic surgery by offering insightful information on the role of AI in delivering value-based healthcare.